Vlogs in L2 listening: EFL learners' and teachers' perceptions. Issue 8 (23rd November 2021) - Aldukhayel, Dukhayel
Abstract: The purpose of this study is to examine the perceptions of EFL learners and teachers toward vlogs as a source of aural input for L2 listening practice inside and outside of classroom. A total of 389 EFL university students drawn from 29 listening/speaking classes and their teachers participated in this study. After four weeks of exploiting vlogs in the classroom, perceptions from students and teachers were collected through questionnaires, focus group-based discussion, and interviews. The findings of this study indicate that students found vlogs engaging, interesting, up-to-date while simultaneously being a source that will ensure learning. Teachers also had positive perceptions toward the use of vlogs in their classes to improve students' listening skill and vocabulary learning, as well as other aspects of the L2.